2016
DOI: 10.1155/2016/8047340
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Doppler, Manual Morphometry, and Histopathology Based Morphometry of Radial Artery as a Conduit in Coronary Artery Bypass Grafting

Abstract: Background. Long-term graft patency is the major factor impacting survival after coronary artery bypass grafting. Arteries are superior in this regard. Radial artery is considered the second best conduit after internal mammary artery. Several studies have shown excellent radial artery patency. We evaluated the morphologic characteristics of radial artery by three modalities, (i) preoperative Doppler ultrasound, (ii) intraoperative manual morphometry, and (iii) postoperative histology-based morphometry, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…A Doppler ultrasound study on 100 subjects who underwent CABG with RA graft demonstrated that intima thickness was more than the proximal [ 13 ], which was similar to our study. In contrast, in a histopathologic study, Ueyma et al showed that the difference in intimal thickness between RA and internal thoracic artery in CABG was non-significant (0.18 vs. 0.26 mm).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A Doppler ultrasound study on 100 subjects who underwent CABG with RA graft demonstrated that intima thickness was more than the proximal [ 13 ], which was similar to our study. In contrast, in a histopathologic study, Ueyma et al showed that the difference in intimal thickness between RA and internal thoracic artery in CABG was non-significant (0.18 vs. 0.26 mm).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, in a histopathologic study, Ueyma et al showed that the difference in intimal thickness between RA and internal thoracic artery in CABG was non-significant (0.18 vs. 0.26 mm). However, the proximal end was slightly larger than the distal [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation